Theory of Resonant Relativistic Oscillator with Non-uniform Focusing Field - Chursin, V. S.; Odarenko, E. N.; Shmat'ko, A. A. (Springer, 1996)
The two-dimensional model of millimeter wave resonant O-type oscillator (as orotron, ledatron, resonant BWO, etc.) with a relativistic electron beam is analyzed. The selfconsistent nonlinear simultaneous equations have been obtained for the arbitrary space distribution of the magnetic guide field. The start generation characteristics are analyzed under small-signal conditions with an analytical solution taken for the case of inclined focusing magnetic field. It is found that the efficiency of electron-wave interaction appreciably depends on the focusing field strength and the relativistic mass factor. The results of numerical optimization of the guide field structure are presented to show possibility of improvement of the start characteristics of the oscillator.
Keywords: O-type electron device; relativistic electron device; two-dimensional nonlinear theory